MEKANISASI PENGIRIS JAHE UNTUK PENINGKATAN PRODUKSI DI UMKM SARI JAMPI - sugati, daru (Retii, 2024)
Mechanization of production equipment in UMKM an effort to increase productivity needs to get attention from higher education academics. UMKM Sari Jampi is an UMKM which operates in the field of processing herbal products. One of the products produced is the wedang uwuh This concoction requires sliced ​​ginger as one of the components in the concoction. The process of slicing ginger from the rhizome into thin flakes has been using a mechanical slicer. This slicing tool has limitations, namely inconsistent thickness, processing time, and the amount of labor. The equipment mechanization process is carried out by changing the driving force from human power to power from an electric motor. The previously reciprocal slicing mechanism has been changed to rotational. The results of this mechanization provide results in the form of thinner and more consistent slice quality, one person is required to work instead of two, and production capacity increases from 4 kg per hour to 20 kg per hour.